Structure, Vibrational Spectra, and Cryogenic MatrixPhotochemistry of 6-Bromopyridine-2-Carbaldehyde: From the Single Molecule of the Compound to the Neat Crystalline Material - Brito, Anna Luiza B.; Lopes, Susy; ILDIZ, GÜLCE ÖĞRÜÇ; Fausto, Rui (MDPI, 2023)
6-Bromopyridine-2-carbaldehyde (abbreviated as BPCA) is used both as a building block in supramolecular chemistry and as a ligand for transition metal catalysts and luminescent complexes. In this study, the structure and vibrational spectra of BPCA were investigated in both the room temperature neat crystalline phase and for the compound isolated in cryogenic Ar, Kr and Xe matrices. The experimental studies were complemented by quantum chemical DFT(B3LYP)/6-311++G(d,p) calculations. For the crystalline compound, infrared and Raman spectra were obtained and interpreted. Comparison of the obtained infrared spectrum of the crystal with those obtained for the isolated molecules of BPCA in the studied cryomatrices helped to conclude that the intermolecular interactions in the crystal do not significantly perturb the intramolecular vibrational potential. Structural analysis further supports the existence of weak coupling between the intermolecular interactions and the structure of the constituting molecular units in crystalline state. The intermolecular interactions in the BPCA crystal were also evaluated by means of Hirshfeld analysis, which revealed that the most important interactions are weak and of the (HN)-N- horizontal ellipsis , (HO)-O- horizontal ellipsis , (HH)-H- horizontal ellipsis , (HBr)-Br- horizontal ellipsis and (BrBr)-Br- horizontal ellipsis types. The conformer of BPCA present in the crystal was found to correspond to the most stable form of the isolated molecule (trans), which bears stabilizing C-(HO)-O- horizontal ellipsis =C and C(=O)(HN)-N- horizontal ellipsis interactions. This conformer was shown to be the single conformer present in the as-deposited cryogenic matrices prepared from the room temperature gaseous compound. Broadband UV irradiation of matrix-isolated BPCA (lambda >= 235 nm) resulted in the conversion of the trans conformer into the higher-energy cis conformer, where repulsive C-(HH)-H- horizontal ellipsis -C(=O) and C=(OLPLPN)-N- horizontal ellipsis (where LP designates a lone electron pair) interactions are present, and decarbonylation of the compound with formation of 2-bromopyridine (plus CO). The decarbonylation reaction was found to be more efficient in the more polarizable Xe matrix, indicating stabilization of the radicals initially formed upon breaking of the C-C(HO) and C-H (aldehyde) bonds in this medium, and testifying the occurrence of the decarbonylation reaction with involvement of radical species. TD-DFT calculations were used to access the nature of the excited states associated with the observed UV-induced reactions. As a whole, this study provides fundamental data to understand the physicochemical behavior of the compound, bridging the properties of the isolated molecule to those of the neat crystalline com-pound. Such information is of fundamental importance for the understanding of the role of BPCA in supramolecular chemistry and to potentiate its applications in synthesis and as a ligand for transition metal catalysts and luminescent complexes.
Keywords: 6-Bromopyridine-2-carbaldehyde; Matrix Isolation; UV–vis; Infrared; Raman and Mass Spectra; Photochemistry; DFT Calculations; Hirshfeld Analysis